(Invited) Effect of Covalent Chemistry on the Electronic Structure and Properties of the Carbon Allotropes. (7th July 2017) - Chen, Mingguang; Tian, Xiaojuan; Pekker, Aron; Li, Wangxiang; Moser, Matthew; Sarkar, Santanu; Wang, Feihu; Stekovic, Dejan; Li, Guanghui; Arkook, Bassim; Kalinina, Irina; Itkis, Mikhail E; et al.
Abstract : We discuss advances in the covalent modification of the carbon allotropes, in particular graphene and carbon nanotubes. The main focus is on the organometallic chemistry that affords the possibility to electronically interconnect graphitic surfaces by means of covalent bonding. This mode of functionalization allows the formation of atomic scale interconnects that consist of bis-hexahapto-metal-bonds between benzenoid ring systems, which increases the dimensionality of the electronic structure of the materials leading to enhanced conductivity. The bis-hexahapto bond formation in single walled carbon nanotubes (SWNTs), graphite nanoplatelets and graphene, can be readily accomplished by metal vapor synthesis (e-beam evaporation), solution and photochemical routes.